Purification, structural characterization, and bioactive properties of exopolysaccharides from Saccharomyces cerevisiae HD-01 - Yang, Ruoxi; Liu, Lina; Gao, Dongni; Zhao, Dan (Frontiers in Bioengineering and Biotechnology, 2024)
Exopolysaccharides (EPSs), which show excellent biological activities, like anti-tumor, immune regulation, and antioxidation, have aroused wide attention. In this study, an EPS-producing Saccharomyces cerevisiae HD-01 was identified based on 18S rDNA sequence analysis and API 20C test. The purified HD-01 EPS was obtained by gel filtration chromatography. High performance liquid chromatography (HPLC), gel permeation chromatography (GPC), fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) revealed that it was heteropolysaccharide composed of α-1 (38.3%), α-1, 2 (17.5%), α-1, 6 (14.8%) linked mannose and α-1, 2, 3, 6 (24.3%), α-1 (3.3%), β-1, 4 (1.8%) linked glucose. Chemical composition and elemental analysis indicated the existence of sulfation modifications. Scanning electron microscope (SEM) and atomic force microscope (AFM) revealed it exhibited a flaky structure with thorn-like protrusions on the three-dimensional surface. X-ray diffraction (XRD) revealed it was an amorphous non-crystalline substance. The HD-01 EPS had great thermostability, probiotic properties, strong antioxidant properties to DPPH, ABTS, hydroxyl, etc., and had good reducing power. The MTT, NO and neutral red assays demonstrated that it had a great immunomodulatory effect on macrophages RAW264.7. All results suggested the HD-01 EPS had the potential to be applied in the food and pharmaceutical fields.